Determinants of bank performance: evidence for Latin America. Issue 2 (29th July 2014) - Jara‐Bertin, Mauricio; Arias Moya, José; Rodríguez Perales, Arturo
Abstract : Purpose: The purpose of this paper is to analyze the impact of macroeconomic‐industrial and bank‐specific factors on Latin American banks' performance. Design/methodology/approach: Using the data panel system estimator version of the generalized method of moments, the authors estimate the determinants of return on assets and interest margin for a sample of 78 commercial banks from Argentina, Brazil, Chile, Colombia, México, Paraguay, Peru, and Venezuela over the period from 1995 to 2010. Findings: On the one hand, the results show that bank performance is positively related to both idiosyncratic factors, such as service diversification, size, capital ratio, and specialization degree, and to macroeconomic‐industrial factors such as economic growth, inflation, and bank concentration. On the other hand, the results show that bank performance is negatively related to credit risk, liquidity risk, and operational inefficiencies. Originality/value: The authors provide new evidence from the Latin American bank industry and incorporate the effect of diversification through noninterest activities.